Edukasi Jajanan Sehat pada Siswa SMAN 35 Jakarta Pusat - Muthia Farah Diba Damanik; Isniati Dwijayanti; Maya Fernandya Siahaan; Dessy Aryanti Utami (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Snacks are one of the main food sources for school children. However, the snacks available in the school environment are sometimes unhygienic and poor in nutrients. This activity aims to increase students' knowledge through education about the importance of healthy snacks. This activity was carried out at SMA Negeri 35 Central Jakarta, on Friday, September 13 2024. The method used was lecture and question and answer sessions. The results of implementing this activity were that students were very enthusiastic, actively asked and answered questions and were able to understand the material about healthy snacks. The evaluation of this educational activity is carried out by providing a questionnaire in the form of closed questions which is given to students before and after education. The results of the activity showed that there was an increase in students' knowledge about healthy snacks after the education was carried out. It is hoped that this activity can help increase students' knowledge about healthy snacks and that students will be able to build the habit of consuming healthy snacks.